THE STATE MANAGEMENT SYSTEM OF THE MASTER AMIR TEMUR (Academicia Globe: Inderscience Research, 2023)
This article talks about state administration, palace positions, and socio-economic relations in the country during the time of Sahibgiron Amir Temur. in addition to the above, this article provides brief information about written sources and historical monuments related to the history of Temur and the Timurid period.